Persepsi Dosen Tetap Di Wilayah Jakarta Barat Dan Tangerang Terhadap Penggunaan E-Filling - Sufiyati, Sofia Prima Dewi, Merry Susanti, (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2019)
This study was made to obtain empirical evidence on the influence of perceptions of security, perceptions of usefulness, perceptions of confidentiality, and perceptions of convenience on the use of e-filling. The method of data collection is done by distributing questionnaires from February to April 2018 to lecturers in the West Jakarta and Tangerang areas. The sampling technique used is simple random sampling. The results showed that perceptions of convenience and perceptions of usefulness have an influence on the use of e-filling while the perception of confidentiality and perception of security have no influence on the use of e-filling.